Comparing immobilisation devices in gynaecological external beam radiotherapy: improving inter‐fraction reproducibility of pelvic tilt - Shimon Prasad; Linda J. Bell; Benjamin Zwan; Florence Ko; Tayla Blackwell; Kevin Connell; Cameron Stanton; Meegan Shepherd; John Atyeo; Mark Stevens; Marita Morgia (Journal of Medical Radiation Sciences)
Abstract Introduction The aim was to determine which immobilisation device improved inter‐fraction reproducibly of pelvic tilt and required the least pre‐treatment setup and planning interventions. Methods Sixteen patients were retrospectively reviewed, eight immobilised using the BodyFIX system (BodyFIX®, Elekta, Stockholm, Sweden) and eight using the Butterfly Board (BB) (Bionix Radiation Therapy, Toledo, OH, USA). The daily pre‐treatment images were reviewed to assess setup variations between each patient and groups for pelvic tilt, pubic symphysis, sacral promontory and the fifth lumbar spine (L5). Results Compared with the planning CT, pelvic tilt for most patients was within ±2° using the BodyFIX and ± 4° for the BB. The Butterfly Board had a slightly higher variance both for patient‐to‐patient (standard deviation of the systematic error) and day‐to‐day error (standard deviation of the random error). Variance in position between individual patients and the two stabilisation devices were minimal in the anterior–posterior (AP) and superior–inferior (SI) direction for the pubic symphysis, sacral promontory and L5 spine. Re‐imaged fractions due to pelvic tilt reduced by about half when BodyFIX was used (39.1% BB, 19.4% BodyFIX). One patient treated with the BB required a re‐scan for pelvic tilt. Three patients required a re‐scan for body contour variations (two using BodyFIX and one with the BB). Conclusions BodyFIX resulted in a more accurate inter‐fraction setup and efficient treatment and is used as the standard stabilisation for gynaecological patients at our centre. It reduced the pelvic tilt variance and reduced the need for re‐imaging pre‐treatment by half.